Peningkatan Kapasitas SDM di Kawasan Ekonomi Khusus (KEK) Mandalika dalam Mendukung event MOTOGP - Surayyal Hizmi; Putri Rizkiyah; Herman; Achlan Fahlevi Royanow; Muhammad Aswad; Nawawi Nawawi (MITRA: Jurnal Pemberdayaan Masyarakat, 2023)
The existence of Mandalika as a Special Economic Zone (SEZ) in Lombok, and as one of the super-priority destinations brings an opportunity to Indonesia, especially to recover from the impact of economic recession due to the Covid-19 pandemic and 8.0 Earthquake in West Nusa Tenggara province. One of the greatest opportunities is the international event of MOTOGP to be held in Mandalika Circuit for about ten years. As a vocational institution, Lombok Tourism Polytechnic conducted several programs to support the acceleration of tourism recovery, especially in the SEZ Mandalika and its supporting areas through increasing the capacity of human resources, particularly in SEZ Mandalika and its surroundings. These programs are workshops in hospitality service, technical guidance in creating foods and beverages from local sources, making beds, and improving skills in a foreign language. There were 120 targeted participants in this activity consisting of security personnel, street vendors, the manager or owner of SARHUNTA and homestays around SEZ Mandalika and its buffer areas. The duration of this project was 6 months, through observation, coordination, programming, implementation of workshop activities and technical guidance as well as gathering feedback from the conducted activities. After conducting the activities, most participants stated that the programs supported and facilitated their work, and they could improve their knowledge and skills in many aspects. However, intensive coaching is needed, especially in small groups to optimize the results of these programs.